Cerdas Bertransaksi: Edukasi Hak Konsumen dalam Penyelesaian Sengketa Belanja Online pada Platform E-Commerce di Kalangan Pelajar - Lestari Wulandari S; Ferinandus Leonardo Snanfi; Rif’iy Qomarrullah; Muhamad Thoif; Milcha H. Tammubua (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
The rapid growth of e-commerce among university students has provided greater convenience in conducting digital transactions. However, it has also created various challenges, including online fraud, discrepancies between advertised and delivered products, delayed shipments, and limited understanding of consumer rights and dispute resolution mechanisms. This community service program aimed to enhance legal literacy and increase students’ awareness of consumer protection in electronic transactions, particularly within the Faculty of Teacher Training and Education (FKIP) of Yapis University Papua. The program employed an educational-participatory approach through counseling sessions, interactive discussions, case simulations, and participant comprehension evaluations. The materials covered consumer rights and obligations, common violations in electronic transactions, complaint procedures on e-commerce platforms, and non-litigation dispute resolution mechanisms. The results demonstrated a significant improvement in students’ understanding of consumer protection laws, their ability to identify violations of consumer rights, and their knowledge of appropriate actions when disputes arise in online shopping transactions. Furthermore, participants showed strong engagement throughout the activities and were able to apply their knowledge effectively during case simulations. The program contributed to the development of more critical, informed, responsible, and legally aware digital consumers who are better prepared to engage safely and confidently in e-commerce activities.